Topical Centella asiatica cream reduces MMP-1 levels but shows limited effect on TIMP-1 in UVB exposed Wistar rats - Citra Dewi Rahayu Setia Wati; Eko Setiawan; Joko Wahyu Wibowo (Published by Universitas Gadjah Mada, 2026)
UVB-induced photoaging accelerates extracellular matrix (ECM) degradation by increasing MMP-1 and suppressing TIMP-1 expression. Centella asiatica, a traditional medicinal herb with antioxidant and anti-inflammatory properties. However, its effect on the MMP-1/TIMP-1 balance under acute UVB exposure hasnot been widely studied. This study aimed to evaluate whether topical C. asiatica extract cream at 5% and 10% concentrations can reduce MMP-1 and increase TIMP-1 in UVB-irradiated Wistar rat. A total of 25 male Wistar rats were randomly assigned to five groups: healthy control, UVB + vehicle, UVB + 5% niacinamide (positive control), UVB + C. asiatica 5%, and UVB + C. asiatica 10%. UVB irradiation (160 mJ/cm²) was administered once daily for five days, with topical application performed 20 minutes before and 4 hours after irradiation. MMP-1 and TIMP-1 levels were measured from skin tissue. UVB exposure significantly increased MMP-1 levels compared to healthy controls (3.100 ± 0.5234 vs. 1.778 ± 0.4081 pg/mL, p < 0.05). The 10% C. asiatica group showed a significant MMP-1 reduction(2.238 ± 0.2705 pg/mL, p < 0.05 vs. UVB + vehicle), comparable to niacinamide. The 5% C. asiatica group showed a non-significant reduction (2.678 ± 0.3148 pg/mL, p > 0.05). TIMP-1 levels did not differ significantly among groups (p = 0.3432), although the 5% C. asiatica and niacinamide groups showed higher TIMP-1 trends. The 10% Centella group had the lowest TIMP-1 levels among treated animals. We conclude that topical C. asiatica extract, especially at 10%, efficiently reduces UVB-induced increase of MMP-1, while its effects on TIMP-1 are still unclear. These results validate C. asiatica’s promise as a topical anti-photoaging drug, necessitating additional research into the best dosage and ECM regulatory mechanisms.